2008
DOI: 10.1016/j.dam.2006.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Counting truth assignments of formulas of bounded tree-width or clique-width

Abstract: We study algorithms for SAT and its generalized version GENSAT, the problem of computing the number of satisfying assignments of a set of propositional clauses . For this purpose we consider the clauses given by their incidence graph, a signed bipartite graph SI( ), and its derived graphs I ( ) and P ( ).It is well known, that, given a graph of tree-width k, a k-tree decomposition can be found in polynomial time. Very recently Oum and Seymour have shown that, given a graph of clique-width k, a (2 3k+2 − 1)-par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
136
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 47 publications
1
136
0
Order By: Relevance
“…By combining these facts, we can conclude that modular incidence treewidth is more general than incidence treewidth. Incidence clique-width is known to be more general than signed incidence clique-width [10]. It is also more general than modular incidence treewidth.…”
Section: Related Structural Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…By combining these facts, we can conclude that modular incidence treewidth is more general than incidence treewidth. Incidence clique-width is known to be more general than signed incidence clique-width [10]. It is also more general than modular incidence treewidth.…”
Section: Related Structural Parametersmentioning
confidence: 99%
“…This parameter is known to be more general than primal treewidth [13]. Again, #SAT on formulas of bounded incidence treewidth is linear-time tractable [10,23]. Clique-width is a graph invariant based on graph grammars [4].…”
Section: Related Structural Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Whence, clique-width can be considered as the most general parameter considered so far. The fixed-parameter tractability of #SAT(cwd) follows from work of Courcelle, Makowsky, and Rotics [5] and that of Oum and Seymour [22], improved by Fischer, Makowsky, and Ravve [8]. Samer and Szeider [25] present dynamic programming algorithms for #SAT(tw) and #SAT(tw * ).…”
Section: Comparisonsmentioning
confidence: 99%
“…A similar time complexity can be achieved by restricting the treewidth of primal graphs and by dynamic programming on tree-decompositions; this approach is described by Gottlob, Scarcello, and Sideri [12] for SAT and can be extended to #SAT as explicated by Samer and Szeider [25]. Bounding the clique-width of directed incidence graphs yields larger classes of formulas for which #SAT is tractable: by combining Oum and Seymour's approximation algorithm for clique-width [22] with a general result of Courcelle, Makowsky, and Rotics [5] on counting problems expressible in a certain fragment of Monadic Second Order Logic, it can be shown that #SAT is fixed-parameter tractable for formulas of clique-width at most k. Fischer, Makowsky, and Ravve [8] improve the constants to obtain an algorithm that solves #SAT in time n O(1) O(f (k)) for formulas with n variables whose directed incidence graphs have clique-width k, where f is a simply exponential function. The latter result is more general than the results for bounded treewidth and branchwidth in the sense that every class of formulas with bounded treewidth or bounded branchwidth also has bounded clique-width; however, there are classes of formulas with bounded clique-width but unbounded treewidth and unbounded branchwidth; see Section 4.…”
Section: Introductionmentioning
confidence: 99%